2008
DOI: 10.1007/s10750-008-9631-6
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic Hemiptera community structure in stormwater retention ponds: a watershed land cover approach

Abstract: Stormwater ponds are increasingly common aquatic habitats whose biotic communities are largely unexplored. As anthropogenic development continues to alter the landscape, watershed land use is gaining recognition for its potential to predict species compositions in aquatic systems. This study reports species composition of five aquatic hemipteran families (Notonectidae, Corixidae, Belostomatidae, Nepidae, Pleidae) in 28 permanent, artificial stormwater ponds in watersheds with different land covers and associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…Another, often unintended, benefit of stormwater ponds is that they serve as wildlife habitat. Previous studies have documented a variety of wildlife species utilizing these habitats, including worms, crustaceans, mussels, insects, fish, amphibians, reptiles, birds, and mammals [2][3][4][5]. Because these ponds are designed to retain sediments and contaminants, wildlife inhabiting stormwater ponds are at risk to being exposed to elevated levels of contaminants [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Another, often unintended, benefit of stormwater ponds is that they serve as wildlife habitat. Previous studies have documented a variety of wildlife species utilizing these habitats, including worms, crustaceans, mussels, insects, fish, amphibians, reptiles, birds, and mammals [2][3][4][5]. Because these ponds are designed to retain sediments and contaminants, wildlife inhabiting stormwater ponds are at risk to being exposed to elevated levels of contaminants [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…We also note that artificial engineered habitats may be especially valuable in the southeastern United States where isolated springs support endemic darters and reproductively specialized minnows (Goldsworthy and Bettoli 2006). And though our interest was in fish, detention ponds can also provide habitat for amphibians (Brand and Snodgrass 2009) and native invertebrates (Foltz and Dodson 2009).…”
Section: Discussionmentioning
confidence: 95%
“…A low fish density within ponds may promote a more diverse macroinvertebrate community through predation of invertebrate predators and larger invertebrate taxa (preferentially eaten by fish as they are more readily seen) (Chaichana et al, 2011) which can reduce the competition for resources and lower invertebrate predation pressure. However, previous research has demonstrated that large predatory fish populations can have a negative effect on macroinvertebrate richness in urban and rural ponds (Diehl, 1992;Nyström et al, 2001;Angélibert et al, 2004;Foltz and Dodson, 2009). It should also be acknowledged that only two of the ponds in this study were stocked for angling purposes (which has been shown to greatly reduce open water macroinvertebrate abundance and diversity (Wood et al, 2001)) and Koi carp and other common ornamental pond species in urban ponds were fed regularly potentially reducing predation on macroinvertebrate taxa.…”
Section: Biological Variablesmentioning
confidence: 90%